The content of nitrogen compounds in the Wel river in the light of the Nitrates Directive - Operacz, Maciej; Kentzer, Andrzej; Nowaczyk, Łukasz (Ecological Questions, 2013)
In this paper, the results of the research are presented on the content and transformation of nitrogen compounds in the Wel River (the largest tributary of the Drwęca River). The catchment area of the studied river is predominantly agriculturally developed. Along the river course, 6 sample collection sites were selected, situated in places with different land development of the drainage basin. The average concentration of total nitrogen in the water of the Wel River amounted to 1.807 mg/dm3, mineral nitrogen - 0.557 mg/dm3 and organic nitrogen - 1.250 mg/dm3. The organic form of nitrogen dominated at all sites (the average content for the whole river amounted to 69%). Nitrate nitrogen dominated in the pool of mineral nitrogen. The lowest concentrations of nitrates were being recorded at lakeland sites, whereas the highest - at two terminal sites situated within the lower reaches of the river, where the drainage basin has a typically agricultural character.